Making Biochar from Palapi Wood Waste (Heritiera sp.) for Decolourisation of Dyes in Water - Razni Razni; Mery Napitupulu; Daud K. Walanda; Detris Poba (Universitas Tadulako, 2025)
Dye waste from industries such as batik can pollute the environment and endanger health because it is carcinogenic. One solution to handle this is to use biochar as an adsorbent, where in this study, the biomass used as biochar is palapi wood waste in the form of wood husks. This study aims to determine the adsorption capacity of biochar from palapi wood waste against indigsol blue and remazol yellow dyes with variations in weight, time, and pH. The method used in this study is the pyrolysis method, namely the process of heating biomass materials at high temperatures without or with little oxygen. Characterization was carried out by determining the water content, ash content, functional groups, and morphology of the biochar. Decolorization efficiency was analyzed using a UV-Vis spectrophotometer. The results showed that the water content at temperatures of 400 ℃, 450 ℃, and 500 ℃ were 11.90%, 6.60%, and 5.30%, respectively. The ash content at the same temperature was 2.30%, 7.50%, and 8.70%, respectively. The maximum weight with variations of 50, 75, 100, and 125 mg in adsorbing 2 dyes is 125 mg with an adsorption percentage of indigosol blue dye of 41.00% and remazol yellow dye of 42.90%. The optimum time for biochar to adsorb indigosol blue dye is 50 minutes, with an adsorption percentage of 47.90, and remazol yellow dye for 40 minutes, with an adsorption percentage of 79.00%. The optimum pH of indigosol blue and remazol yellow dyes by biochar occurs at pH 7, with an adsorption percentage of indigosol blue dye of 93.03% and remazol yellow dye of 87.40%. The absorption capacity of biochar for indigosol blue and remazol yellow dyes follows the Langmuir absorption isotherm of 0.92 mg/g and 0.79 mg/g, respectively.